Some characteristics of recurving cyclones of the Indian seas - JAYANTHI, N. (MAUSAM, 2000)
The present study deals with some of the characteristics of recurving cyclones of the Indian seas like speed, intensity and latitude of recurvature etc. The synoptic features, which are responsible for recurvature, are also studied. Analysis of 200 hPa wind composites indicates some predictive signature atleast 24 hours (IST) prior to recurvature.